COVID-19 Vaccine Uptake Inequality Among Adults: A Multidimensional Demographic Analysis - Seyed M. Karimi; Mana Moghadami; Md Yasin Ali Parh; Shaminul H. Shakib; Hamid Zarei; Venetia Aranha; Sepideh Poursafargholi; Trey Allen; Bert B. Little; Demetra Antimisiaris; W. Paul McKinney; Yu-Ting Chen; et al. (COVID)
Adults face a higher risk of exposure to COVID-19 than older adults and children due to their labor force participation. This study investigated the uptake of the initial and second doses of the COVID-19 vaccine among adults, stratified by age, race, ethnicity, sex, and their combinations. Data from the Kentucky Immunization Registry were employed to evaluate temporal changes in COVID-19 vaccine uptake among adults in three age groups (college age: 18–24, prime working age: 25–44, and middle age: 45–64) in Jefferson County, Kentucky (2020 population: 782,969). The analysis explored trends by age, race, and ethnicity; intersections of age with race and ethnicity; and interactions of age–race and age–ethnicity with sex. By May 2022, the highest and lowest COVID-19 vaccination rates were observed among White and Black 45–64-year-old adults: 74.8% and 64.0%, respectively, for dose two. The highest and lowest two-dose vaccination rates at ages 25–44 and 18–24 were also among White and Black residents: 67.9% versus 46.0% and 55.2% versus 35.4%, respectively. Disparities in COVID-19 vaccination by race, ethnicity, sex, and their intersections remained evident during the study period. Efforts in vaccine distribution and promotional initiatives should focus on demographically appropriate strategies.